Amoeba quality of bottled water in carboy of the metropolitan area of Mexico City - Ramírez Flores, Elizabeth; Robles Valderrama, Esperanza del Socorro; Sáinz Morales, María De Guadalupe; Martínez Rodríguez, Blanca Nieves; Vargas Cerón, Brian Guadalupe; Ramírez Flores, Miguel Ángel (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2022)
Mexico stands on the first position in the world about the consumption of bottled water per cápita. The consumption has been increased due to the bad quality of the water given by the supply network and the unequal and intermittentaccess to it. The contamination of the bottled water by bacteria has been reported all around the world, but it has not been investigated the presence of other microorganisms, like pathogenic free-living amoebae, which can be present in the environment, furthermore they can cause infections to humans. The objective of this investigation was to determine the presence of free-living amoebae in bottled water. Water of 47 twenty-liter carboys sold in the metropolitan area ofMexico City was analyzed. Two samples from each carboy were taken, one immediately after opening it and the other when it had reached the half of its volume. The amoebae were determined by cultivation in nonnutritive agar and wereidentified by morphology. Thirty-one carboys were positive for the presence of amoeba, of these, twenty-one were from local water purifiers and ten were from big water purifiers. Fifteen species were found, most of them have not been reported as pathogenic. Only Acanthamoeba has been reported as an opportunistic pathogen. The presence of this amoeba represents a health risk for the people with a weakened immune system. Because of this, not only the bacteriological and physicochemical quality but also amoeba quality must be considered.